The Application of the Ansoff Matrix in Dental Business Management - Alessandro Quaranta; Wang Lai Hui (Publymed, 2024)
This paper examines the implementation of the Ansoff Matrix, a well-established framework for strategic planning, in the management of dental businesses. It explores how the four growth strategies delineated by the matrix-market penetration, market development, product development, and diversification-can be effectively utilized by dental practices to expand and thrive within the evolving healthcare landscape.